1992
DOI: 10.1111/j.1365-2222.1992.tb00154.x
|View full text |Cite
|
Sign up to set email alerts
|

Oilseed rape—a new allergen?

Abstract: Oilseed rape (Brassica napus) is a commonly grown crop in Europe and it has been suggested that its pollen may be a potent new allergen. The prevalence of sensitization in a normal exposed population and an objective study of those patients found to be allergic to the rape pollen is described. The results show a low prevalence of allergy to oilseed rape pollen (less than 0.2%) unless the subjects were occupationally exposed. Those affected, with one exception, were already atopic and allergic to other pollens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 15 publications
0
38
0
Order By: Relevance
“…Therefore, allergy to Brassica or Lilium pollen is uncommon in the population. However, epidemiological studies showed that the incidence of Brassica pollen allergy is much higher in individuals occupationally exposed to Brassica pollen (54).…”
Section: Iontophoresis Of Bet V 4 Into Growing Lilymentioning
confidence: 99%
“…Therefore, allergy to Brassica or Lilium pollen is uncommon in the population. However, epidemiological studies showed that the incidence of Brassica pollen allergy is much higher in individuals occupationally exposed to Brassica pollen (54).…”
Section: Iontophoresis Of Bet V 4 Into Growing Lilymentioning
confidence: 99%
“…These molecules were identified by their ability to bind to human IgE. As oilseed rape pollen allergy is not a well-defined entity, we chose to test human sera from birch- and/or orchard grass-allergic patients because the pollinic season of oilseed rape and birch overlap in spring [2]. The other patients, who were allergic to mustard, were chosen because mustard belongs to the Brassicaceae, as does oilseed rape.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1954, several reports have examined the question of the potential role of oilseed rape (Brassica napus) in pollen allergy [1, 2, 3, 4, 5, 6, 7]. Some of them concluded that type I hypersensitivity to rape pollen is limited to atopic patients with a history of pollen allergy [2, 3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While complaints attributed to OSR cultivation have been considered to be caused by irritant rape volatiles, such as terpenes, which are produced in high quantities by the plant for insect attraction or natural pathogen defense [3, 4], it has been known for nearly 50 years that OSR pollen may sensitize and provoke allergic symptoms [5]. Recent studies revealed conflicting results regarding the prevalence of OSR allergy but consistently proved the possibility of allergic sensitization to its pollen [1, 2, 6, 7]. The cultivation of the closely related species B. rapa (= campestris, turnip rape) has been recognized for years as a cause of allergic disease in India [8], and sensitization was also described from Japan [9].…”
Section: Introductionmentioning
confidence: 99%